Different risk assessment methodologies applied for infant's exposure for polybrominated diphenyl ethers: Implications for public health. Issue 7 (29th July 2021) - Hernik, Agnieszka; Liszewska, Monika; Struciński, Paweł; Robson, Mark G.; Rybińska-Piętowska, Malwina; Czaja, Katarzyna; Korcz, Wojciech
Abstract: The study aimed to determine the levels of selected polybrominated diphenyl ethers (PBDEs) in human milk and characterize the risk for breastfed infants using EFSA and U.S. EPA methodologies. The predominant PBDEs for which EFSA and U.S. EPA established toxicological reference values have been selected for evaluation. Concentrations of BDE-47, BDE-99 and BDE-153 were determined in breast milk samples from 25 mothers living in Poland. The estimated daily intakes of PBDEs for breastfed infants were calculated based on the results of PBDE concentrations obtained for each case and for the mean concentrations of the analyzed compounds. The estimated infants' daily intake of PBDEs from human milk was below U.S. EPA RfD, therefore not considered a health risk. In calculations according to approach applying MOEs (EFSA), we indicated a potential health concern with respect to exposure of infants to BDE-99. The calculated results based on the available methodologies do not provide clear information for the purposes of consumer safety assessment regarding exposure to the BDE-99 congener. Present study indicates the necessity to develop an internationally harmonized strategy for assessing the risk posed by polybrominated diphenyl ethers, especially for breast-fed infants.